OCENIANIE W NAUCZANIU JĘZYKÓW OBCYCH. FAKTY, MITY I TRUDNOŚCI - Hanna Komorowska, (Neofilolog, 2019)
The article presents selected psychological and sociological aspects of the process of evaluating educational attainment in language education. Attention is given to stereotypical and ahistorical opinions connected with the role of assessment in grammar-translation and audiolingual methods as well as in the communicative approach. Distortions are also discussed such as introducing testing techniques of a practical value in mass education as solutions responding to authentic communicative needs of the learners or presenting formative evaluation as one of the recent educational innovations. Several myths which unify the academic community and facilitate interaction are examined and distinguished from complex issues and difficulties such as assessing intercultural competence or objectivizing the evaluation of interactive skills. The text suggests that misrepresentation of the past serves to create an image of continuous progress in SLA/FLT as well as to paint a more optimistic picture of the present educational context with assessment as its integral element.